(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The study was carried out in 5 Upazilas under Chittagong district with a view to analyze the present socio-economic status of RCC farming practices on 100 RCC rearers (Potiya, Raujan, Chandanaish, Anowara and Satkania Upazila). The study showed that, about 39.00 percent of RCC farm owners were landless, 31.00 percent were small and marginal farmers, 17.00 percent were medium and 13.00 percent were large farmers according to their landholding sizes. The cost of rearing RCC per cattle per year was found to be Tk. 17503.76, Tk. 15540.27, and Tk. 33044.03 as cash cost, non cash cost and total cost respectively. The study also revealed that, average daily milk yield, lactation yield and lactation length of RCC were found to be 2.71 liters, 581.61 liters and 215.41 days, respectively. The average per year per cattle gross return of RCC was found Tk. 25390.41. The gross returns over cash cost and full cost basis of rearing per lactation per cattle of RCC were found at Tk 8058.642 and Tk.-7501.53, respectively. The benefit cost ratio on the basis of cash cost and full costs per year per cattle was found 1.47 and 0.77, respectively. The study also revealed that, the rural farmers prefer RCC farming than other breeds due to high conception rate, each year calving, disease resistance, high milk fat per cent and cost effective farming. Keyword: RCC; Cost; Return; Profitability; Disease Occurrences DOI: 10.3329/jbau.v8i2.7937 J. Bangladesh Agril. Univ. 8(2): 271-276, 2010